2021
DOI: 10.2174/1386207323666201211102233
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Melanogenesis by Some Well-Known Polyphenolics: A Review

Abstract: : Melanogenesis is simply defined as production of melanin in melanosomes by melanocytes through a complex process. Melanin, a pigment derived from L-tyrosine, comes into two forms, namely eumelanin (brownish to black) and pheomelanin (red to yellow). Melanin synthesis starts via the hydroxylation of L-tyrosine to L-3,4-dihydroxyphenylalanine (DOPA) catalyzed by the enzyme known as tyrosinase (TYR), which triggers further conversion reaction to DOPAquinone and then to DOPAchrome. Additionally, this process is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Both sequences possess the tyrosinase and hemocyanin CuB-binding region signature D-P-x-F-[LIVMFYTW]-x(2)-H-x(3)-D and the CuA-binding region signature H-x(4,5)-F-[LIVMFTP]-x-[FW]-H-R-x(2)-[LVMT]-x(3)-E ( Figure 2 and Figure 3 ). According to a previous study, seven histidine residues (His180, His202, His211, His363, His367, His389, His390) participate in copper chelation and substrate binding [ 10 , 53 ]. Human tyrosinase possesses the EGF domain ( Figure 2 and Figure 3 ), which is absent in the mushroom tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Both sequences possess the tyrosinase and hemocyanin CuB-binding region signature D-P-x-F-[LIVMFYTW]-x(2)-H-x(3)-D and the CuA-binding region signature H-x(4,5)-F-[LIVMFTP]-x-[FW]-H-R-x(2)-[LVMT]-x(3)-E ( Figure 2 and Figure 3 ). According to a previous study, seven histidine residues (His180, His202, His211, His363, His367, His389, His390) participate in copper chelation and substrate binding [ 10 , 53 ]. Human tyrosinase possesses the EGF domain ( Figure 2 and Figure 3 ), which is absent in the mushroom tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it has been suggested that melanin production is primarily controlled by the expression and activation of tyrosinase. Therefore, the main strategy is to target tyrosinase, with increasing interest in the use of natural products as tyrosinase inhibitors [11,12]. The established murine B16 melanoma cell (B16F10 cells) line offers a model system with readily quantifiable markers characteristic of differentiation, including melanogenesis [21].…”
Section: Jnucc6 Extract Inhibits Melanin Production and Tyrosinase Ac...mentioning
confidence: 99%
“…Moreover, green and environmentally friendly organic products have become popular. Ultimately, research and discovery of safe and healthy skin-whitening ingredients have become a trend in modern development [11,12]. Hyperpigmentation is one of the most common skin diseases that affects both men and women of all ethnic groups owing to a number of factors, such as ultraviolet (UV) exposure and skin inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Based on the knowledge of this enzymatic pathway, the targeting of tyrosinase inhibitors (TYRIs) has demonstrated efficacy in cosmetic and dermatology applications. 4 To address this issue, a large number of inhibitors from natural and synthetic sources have been reported in the literature; 1,[5][6][7] they have generally been identified on the basis of their ability to inhibit tyrosinase from Agaricus bisporus (AbTYR), which represents a readily and cheap protocol to preliminarily screen TYRIs. 8,9 In turn, the best active AbTYR inhibitors were further studied using advanced biological methods, as well as human tyrosinase (hTYR) screening validation through cell-free crude extracts of tyrosinase-expressing cell lines and recombinant hTYR.…”
Section: Introductionmentioning
confidence: 99%